2018
DOI: 10.3390/genes9080413
|View full text |Cite
|
Sign up to set email alerts
|

Proteome-Wide Analysis of Trypanosoma cruzi Exponential and Stationary Growth Phases Reveals a Subcellular Compartment-Specific Regulation

Abstract: Trypanosoma cruzi, the etiologic agent of Chagas disease, cycles through different life stages characterized by defined molecular traits associated with the proliferative or differentiation state. In particular, T. cruzi epimastigotes are the replicative forms that colonize the intestine of the Triatomine insect vector before entering the stationary phase that is crucial for differentiation into metacyclic trypomastigotes, which are the infective forms of mammalian hosts. The transition from proliferative expo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 102 publications
1
32
0
1
Order By: Relevance
“…cruzi, like other dixenous trypanosomatid parasites, undergoes an elaborate life cycle involving extracellular replicative epimastigotes in the triatomine digestive tube, non-replicative extracellular metacyclic and bloodstream trypomastigotes in the insect and mammalian host, respectively, and replicative amastigotes intracellularly in the cytosol of the mammalian cells. The different developmental stages differ importantly in morphology, but also in metabolism to adapt to the large nutritional conditions encountered in the different niches (Maugeri et al, 2011;Barisón et al, 2017;Avila et al, 2018;Marchese et al, 2018;Mattos et al, 2019). Since glycosomes harbor many enzymes of intermediary metabolism as well as enzymes of other metabolic processes which are differentially expressed, glycosomal metabolism has to undergo reprogramming.…”
Section: Glycosomal Reprogramming During Differentiation Of Trypanosomesmentioning
confidence: 99%
“…cruzi, like other dixenous trypanosomatid parasites, undergoes an elaborate life cycle involving extracellular replicative epimastigotes in the triatomine digestive tube, non-replicative extracellular metacyclic and bloodstream trypomastigotes in the insect and mammalian host, respectively, and replicative amastigotes intracellularly in the cytosol of the mammalian cells. The different developmental stages differ importantly in morphology, but also in metabolism to adapt to the large nutritional conditions encountered in the different niches (Maugeri et al, 2011;Barisón et al, 2017;Avila et al, 2018;Marchese et al, 2018;Mattos et al, 2019). Since glycosomes harbor many enzymes of intermediary metabolism as well as enzymes of other metabolic processes which are differentially expressed, glycosomal metabolism has to undergo reprogramming.…”
Section: Glycosomal Reprogramming During Differentiation Of Trypanosomesmentioning
confidence: 99%
“…Otherwise, this paper reported the regulation of N-terminally acetylated proteins during growth phase transitioning, adding a new layer of regulation to this process. Thus, this paper reported a proteome-wide rewiring during T. cruzi differentiation from the EPIs' proliferative exponential phase to the stationary growth phase, which is the step before cell transformation into the MT stage [36].…”
Section: T Cruzi Subcellular Proteomicsmentioning
confidence: 91%
“…Next study indicated that during periods of nutritional stress, many proteins are phosphorylated, which may trigger metacyclogenesis [ 150 ]. Similarly, the proteomic comparison of the exponential phase and stationary phase of the epimastigotes quantified more than 3000 proteins [ 151 ]. The transition from trypomastigotes to amastigotes (amastigogenesis) was described by quantitative proteomics and phosphoproteomics [ 152 , 153 ].…”
Section: Discovery Approach—description Of the Selected Fbps And Tmentioning
confidence: 99%